A New Blend of Litsea cubeba, Pinus mugo, and Cymbopogon winterianus Essential Oil Active as an Anti-tyrosinase Ingredient in Topical Formulations - Capetti, Francesca; Cagliero, Cecilia; Argenziano, Monica; Cavalli, Roberta; Dianzani, Chiara; Pavarino, Marta; Bicchi, Carlo; Rubiolo, Patrizia; Sgorbini, Barbara (Planta Medica, 2024)
Tyrosinase is a target enzyme to be inhibited in order to reduce excessive melanin production and prevent typical age-related skin disorders. Essential oils are complex mixtures of volatile compounds, belonging mainly to monoterpenoids and sesquiterpenoids, which have been relatively little studied as tyrosinase inhibitors. Among the monoterpenoids, citral (a mixture of neral and geranial) is a fragrance compound in several essential oils that has shown interesting tyrosinase inhibitory activity. Although citral is listed as an allergen among the 26 fragrances in Annex III of the Cosmetics Directive 2003/15/EC, it can be safely used for the formulation of topical products in amounts that are not expected to cause skin sensitization, as shown by various commercially available products.The aim of this work was to evaluate two different formulations (oil/water emulsion, oily solution) containing a new combination of essential oils (Litsea cubeba, Pinus mugo, Cymbopogon winterianus) applied to the skin both in nonocclusive and partially occlusive modes. The blend is designed to reduce the concentration of citral to avoid potential skin reactions while taking advantage of the inhibitory activity of citral. Specifically, the amount of citral and other bioactive compounds (myrcene, citronellal) delivered through the skin was studied as a function of formulation and mode of application.The results show that an oil/water emulsion is preferable because it releases the bioactive compounds rapidly and minimizes their evaporative loss. In addition, semi-occluded conditions are required to prevent evaporation, resulting in higher availability of the bioactive compounds in viable skin.
Keywords: essential oils; dermal permeation; Litsea cubeba; Lauraceae; Pinus mugo; Pinaceae; Cymbopogon winterianus; Poaceae